2020
DOI: 10.1155/2020/8881898
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Microstructure and Bonding Properties of Zirconium-Carbon Steel Clad Materials by Explosive Welding

Abstract: An investigation was carried out to characterize the microstructure and bonding properties of the zirconium-carbon steel explosive clad. The microstructure and the composition of the clad were characterized using optical microscopy and scanning electron microscopy. Bonding properties were inspected by using bending and shearing tests. The examination results indicate that the R60702 and Cr70 plates were joined successfully without visible defects. The interface wave is symmetrical. There is no element diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Metals 2022, 12, x FOR PEER REVIEW 2 of 10 materials [7][8][9]. Titanium-steel clad materials possess both titanium and steel advantages (high strength and toughness, reduce costs as well as high corrosion resistance).…”
Section: Explosive Welding Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Metals 2022, 12, x FOR PEER REVIEW 2 of 10 materials [7][8][9]. Titanium-steel clad materials possess both titanium and steel advantages (high strength and toughness, reduce costs as well as high corrosion resistance).…”
Section: Explosive Welding Processmentioning
confidence: 99%
“…Ultrasonic examination (UT) was employed to inspect the clad plates using OLYMPUS 5077 equipment [7]. During the UT process, the bonding interface image was obtained using ultrasonic C-scanning imaging technology.…”
Section: Specimen Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Explosive welding is noted for its capability of offering high strength bonding and cladding metals that are unweldable or are difficult to weld by other methods. It has been developed as a promising way to clad dissimilar materials [5][6][7][8][9][10][11][12][13]. Thus, some attempts have been made to clad other materials on Mg alloys by explosive welding.…”
Section: Introductionmentioning
confidence: 99%
“…Optical microscopy (OM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), electron backscatter diffraction (EBSD), energy dispersive spectroscopy (EDS) and numerical simulation can be used to study their formation and evolution. Previous studies have found that collision produces molten metal flow, mixing and element diffusion, which is an important cause of the formation of molten blocks [5,10]. This high temperature and diffusion results in metallurgical bonding of the composite plate [12], at the same time, element diffusion is beneficial to the bonding strength of composite plates [11].…”
Section: Introductionmentioning
confidence: 99%